A Peptide‐Induced Self‐Cleavage Reaction Initiates the Activation of Tyrosinase - Kampatsikas, Ioannis (Angew Chem Int Ed Engl, 2019)
The conversion of inactive pro‐polyphenol oxidases (pro‐PPOs) into the active enzyme results from the proteolytic cleavage of its C‐terminal domain. Herein, a peptide‐mediated cleavage process that activates pro‐MdPPO1 (Malus domestica) is reported. Mass spectrometry, mutagenesis studies, and X‐ray crystal‐structure analysis of pro‐MdPPO1 (1.35 Å) and two separated C‐terminal domains, one obtained upon self‐cleavage of pro‐MdPPO1 and the other one produced independently, were applied to study the observed self‐cleavage. The sequence Lys 355–Val 370 located in the linker between the active and the C‐terminal domain is indispensable for the self‐cleavage. Partial introduction (Lys 352–Ala 360) of this peptide into the sequence of two other PPOs, MdPPO2 and aurone synthase (CgAUS1), triggered self‐cleavage in the resulting mutants. This is the first experimental proof of a self‐cleavage‐inducing peptide in PPOs, unveiling a new mode of activation for this enzyme class that is independent of any external protease.